Madonna. - Madonna, Madonna Louise Ciccone; Warner Bros. (United States : Warner Bros, 1998)
Contains single taken from the album Ray Of Light.
CD 1 : Ray Of Light / (5:21) -- Shanti/Ashtangi / (4:29)
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Rock music